2012
DOI: 10.1093/humrep/des036
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric outcome in singletons after in vitro fertilization with cryopreserved/thawed embryos

Abstract: The obstetric outcome of singletons after cryopreservation was slightly poorer when compared with the general population. In comparison with fresh cycles, the outcome varied. The finding of an increased rate of LGA after cryopreservation requires further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
158
6
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 223 publications
(187 citation statements)
references
References 30 publications
17
158
6
6
Order By: Relevance
“…These analyses indicate that frozen embryo state [4][5][6][7][8][9][10][11][12][13] is associated with an increased risk for LGA, and blastocyst embryo stage is associated with a decreased risk for SGA. The magnitude of the increase we found in the 2nd birthweight in the fresh/frozen pairs of siblings of +222 g is in accord with prior studies (+244 g 4 in an Australian population, +250 g 10 and +286 g 6 in Danish populations), and far exceeds the +81 g attributable only to an increase in parity.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…These analyses indicate that frozen embryo state [4][5][6][7][8][9][10][11][12][13] is associated with an increased risk for LGA, and blastocyst embryo stage is associated with a decreased risk for SGA. The magnitude of the increase we found in the 2nd birthweight in the fresh/frozen pairs of siblings of +222 g is in accord with prior studies (+244 g 4 in an Australian population, +250 g 10 and +286 g 6 in Danish populations), and far exceeds the +81 g attributable only to an increase in parity.…”
Section: Discussionmentioning
confidence: 88%
“…Prior studies have also consistently reported an excess of large-for-gestational age (LGA) birthweights among children born from frozen embryos; [4][5][6][7][8][9][10][11][12] longer embryo culture of fresh embryos has also been implicated as a potential cause of LGA [13].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have confirmed that there are important differences in placental abnormality rates between FET and fresh ET singleton pregnancies [3,6,7,13] and that placentas after IVF are larger and heavier [28]. In a recent study, the researchers speculated that increased placental size could promote glucose delivery to LGA fetuses [48].…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have shown that singletons born after FET have a perinatal outcome more comparable to those born after natural conception than to those born after fresh embryo transfer (fresh ET), having higher birth weight and less pregnancy complications [2][3][4][5][6][7][8][9][10]. However, higher risk for birth of a singleton being large for gestational age (LGA) has been revealed after FET [2,3,7,8,[11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation